Prvoosebna fenomenološka študija samogenerirane slepote - Kermauner, Aksinja (Revija za elementarno izobraževanje, 2011)
Firsthand Phenomenological Study of Selfgenerated Blindness. The paper presents the results of qualitative research done on self-generated blindness. The study was based on phenomenological research work and the introspective method – first person observation. The nominal data that I acquired, being a blind person, are codified and categorized according to the research and the analysis of other observations that were also made. A comparison was made between the results of the experiment and the results gained from interviewing recently blinded adults. The experiment was repeated according to the achieved categories and was performed in compliance with the phenomenological procedures of research work. The goals for researching this topic firsthand are as follows: to try to contribute new knowledge about the domains of specific experiences a blind person, to contribute to the theory of teaching orientation and mobility, to help recognize the psychological characteristics of blind people for the understanding of their behaviour in certain situations related to blindness, and to enrich this particular pedagogical field. Firsthand reasearch should also contribute to the implementation of firsthand scientific research as an important approach towards the understanding of the experiences of people who are different.
Keywords: phenomenology; first person research; blindness; sense of touch